The Paradox of Plenty in Zakat Management: Baitul Mal Hidayatullah’s Financial Sustainability and Effectiveness - Ananda Ayu Amelia; Desmadi Saharuddin; Rahmat Hidayat; Abdul Hamid (Maliki Islamic Economics Journal, 2026)
This study examines the paradox between Indonesia's substantial zakat potential and its institutional realization by assessing the financial sustainability and distribution effectiveness of Baitul Mal Hidayatullah. Using secondary data from audited financial statements and institutional reports, the study analyzes zakat collection and distribution through the Allocation to Collection Ratio (ACR), complemented by descriptive statistics, Ordinary Least Squares (OLS) regression, and Pearson correlation analysis. The findings indicate that zakat collection fluctuated considerably, whereas distribution remained consistently high, with ACR exceeding 100% in two years due to reserve utilization. Regression results reveal that distribution volume significantly improves ACR performance, while collection growth alone does not proportionally enhance distribution effectiveness. These findings highlight a structural imbalance between fundraising capacity and sustainable fund allocation. The study implies that zakat institutions should strengthen reserve management, improve fundraising sustainability, and enhance financial governance to maintain long-term institutional resilience. This study is limited to a single national zakat institution and a five-year observation period; therefore, future studies should employ comparative analyses across multiple institutions and incorporate broader governance and macroeconomic variables.